Function of Transient Receptor Potential-Like Channel in Insect Egg Laying - Zhang, Yan; Zhang, Yi-Jie; Guo, Di; Wang, Li-Xiang; Niu, Chun-Dong; Wu, Shun-Fan; Zhang, Yali V.; Gao, Cong-Fen (Frontiers in Molecular Neuroscience, 2022)
The transient receptor potential-like channel (TRPL) is a member of the transient receptor potential (TRP) channel family involved in regulating many fundamental senses, such as vision, pain, taste, and touch, in both invertebrates and vertebrates. Yet, the function of TRPL in other important biological processes remains unclear. We discover that TRPL regulate egg laying in two insect species, the brown planthopper, Nilaparvata lugens, and the fruit fly, Drosophila melanogaster. In both insects, trpl is expressed in the female reproductive organ. Loss of trpl leads to significantly impaired in egg laying. In addition, TRPL is functionally interchangeable between the brown planthoppers and flies in egg laying. Altogether, our work uncovers a novel role played by TRPL in regulating egg laying and suggests TRPL as a potential pesticide target to control reproduction in brown planthoppers.